Meningkatkan Ketuntasan Hasil Belajar IPA menggunakan Model Pembelajaran Problem Solving pada Siswa Kelas 5 - Muhafid, Ervian Arif; Widyawati, Eva (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The aim of this research is to enhance students' learning outcomes in Science subjects using the problem-solving learning model. The research method employed is Classroom Action Research comprising four stages: planning, implementation, observation, and reflection. The research subjects are eight fifth-grade students of SDN 3 Tugu, consisting of 3 males and 5 females. Data analysis techniques include regression analysis and descriptive analysis. Based on the discussion and research findings, it can be concluded that the problem-solving learning model accompanied by video media can improve the learning outcomes of fifth-grade students at SDN 3 Tugu in the subject of Science, specifically in the topic of technology for life. The achievement percentage from pre-cycle to Cycle II shows an enhancement in students' learning outcomes: pre-cycle average score of 61.5 (25%), Cycle I average score of 66.5 (50%), and Cycle II average score of 84 (87.5%). The increase in teacher activity from 79% in Cycle I to 96% in Cycle II is observed. Meanwhile, the comparison of student activities indicates an increase from 70.7% in Cycle I to 94.8% in Cycle II, suggesting that problem-solving learning is effective in teaching.